Factors Influencing on Managerial Ability of Administrators and Board of Directors in Agricultural Production Cooperatives of Harsin Township - Akram Binaian; Amir Hossein Ali Beigi; Afsaneh Malek Hosseini; Hassan Heidari; Ehsan Zarei (تعاون و کشاورزی, 2015)
The main purpose of this descriptive- correlational research was to identify the factors influencing on Managerial ability of administrators and board of directors of agricultural production cooperatives. The statistical population consisted of all administrators and board of directors of agricultural production cooperatives in Harsin Township (N=444). Samples were selected using stratified sampling technique (n= 206). Based on findings, the managerial ability of respondents was at moderate level.  The locus of control of the majority was internal. It means that they attribute their successes and failures to themselves. Based on exploratory factor analysis the main managerial styles of participants were regulated, inefficient and participatory. The most important factors affecting on managerial ability were locus of control, educational level, goal of cooperation and sustainability and participatory management style.